Estratégias integradas de modificação de nanopartículas de óxido de zinco aplicadas à redução eletroquímica de CO2 a CO - Nóbrega, Eryka Thamyris Damascena (Universidade Federal de São Carlos, 2026)
Anthropogenic carbon dioxide (CO2) emissions represent one of the major environmental challenges of the present time, driving the development of strategies aimed at integrating carbon into sustainable chemical cycles. In this context, the electrochemical reduction of CO2 into value-added products, particularly carbon monoxide (CO), has emerged as a promising alternative. In this work, ZnO-based systems modified with Co2+, Ag+, and Cu2+, as well as Ag+/Cu2+ co-modified materials, were investigated. The catalysts were synthesized through a hydrothermal route assisted by microwave heating and UV-Vis radiation. The experimental strategy was supported by chemometric tools, enabling a statistically robust evaluation of the main effects and interactions among chemical composition, synthesis conditions, and operational parameters. The materials were characterized using structural, morphological, and electronic techniques. Electrochemical performance was evaluated in cells operating under continuous CO2 flow, employing gas diffusion electrodes and different applied potentials or current densities. Reaction products were quantified by chromatographic analysis, allowing the determination of Faradaic efficiencies. For the Co2+-doped ZnO system, cobalt incorporation induced significant changes in the electronic structure, including a reduction in charge carrier density and the introduction of deep defect states. These modifications hindered electronic transport at low overpotentials, resulting in lower selectivity toward CO. Although synthesis assisted by UV-Vis radiation modulated the nature of these defects and favored charge migration at more negative potentials, pristine ZnO synthesized without UV-Vis irradiation exhibited the best performance, reaching Faradaic efficiencies close to 97% for CO at more negative potentials, such as -1.0 V vs. RHE. In systems modified with Ag+, Cu2+, and Ag+/Cu2+, the presence of Ag+ proved particularly effective in improving the electrocatalytic performance of ZnO. ZnO(Ag) catalysts achieved Faradaic efficiencies above 80% for CO even at high current densities (up to -100 mA cm-2). This behavior is attributed to improved charge transport, enhanced CO2 adsorption, and greater stabilization of reaction intermediates. In contrast, Cu-containing materials exhibited lower selectivity toward CO, although they promoted the formation of minor products, suggesting modifications in reaction pathways and the possible promotion of competing routes. The Ag+/Cu2+ systems showed intermediate behavior, indicating that the synergistic effect between the metals strongly depends on their relative proportion and surface distribution. Overall, the results demonstrate that the electrocatalytic performance of ZnO is governed by a complex interplay between metal incorporation, synthesis method, and operational conditions.
Integrated strategies for modifying zinc oxide nanoparticles applied to the electrochemical reduction of CO2 to CO
Keywords: Redução eletroquímica de CO2; Óxido de zinco; Dopagem metálica; Síntese fotoassistida; Quimiometria; CO2 electroreduction; Zinc oxide; Metal doping; Photo-assisted synthesis; Chemometrics; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA::ELETROQUIMICA; 7. Energia limpa e acessível; 9. Indústria, Inovação e Infraestrutura; 12. Consumo e Produção Responsáveis; 13. Ação contra a Mudança Global do Clima